THE EFFECT OF POROSITY LEVEL ON THE NUMBER OF MYCORRHZA SPORES AND THE LENGTH OF CATTLE CHILI ROOTS - Nabillah Anissa; Lamdo, Herfandi (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2025)
Porosity is the proportion of total pore space or empty space in a unit volume of soil that can be occupied by water and air (Hanafiah, 2015). Solid soil will interfere with plant root penetration so that plant growth (Haridjaja et al., 2010). Appropriate soil porosity can optimize the increase of mycorrhizal spores. High oxygen content can increase the spores. Flooded soil has little pore space so the oxygen content is low which causes the development of mycorrhizal spores to be low (Gustian et al., 2015). Research needs to be carried out to determine the best soil porosity for increasing of mycorrhizal spores and cayenne pepper root growth. The research hypothesis is that different levels of porosity influence the mycorrhizal spores and the root length of cayenne pepper plants. Research was the Satu Nusa Lampung University Greenhouse and the Soil Science Laboratory, Lampung State Polytechnic. The research was conducted from July to October 2024. The research used RAL repeated 5 times to obtain 25 total treatments. Each treatment consisted of 4 plants so there were 100 plants. Very poor porosity (P1), poor porosity (P2), poor porosity (P3), good porosity (P4) and porous porosity (P5). The results of the research show that different levels of porosity have a significant effect on the mycorrhizal spores and the root length of cayenne pepper plants. The best level of porosity was porous porosity with a number of spores of 25.70 g and cayenne pepper plant root length of 32.90 cm. Keyword: Cayenne pepper, mycorrhizal, porosity